Evaluating Environmental Sustainability Practices in Bank Syariah Indonesia: Green Banking and Maqashid al-Syari’ah: - Vani Febiola; Muhammad Iqbal Fasa; Suharto Suharto (Econetica: Jurnal Sosial, Ekonomi, dan Bisnis, 2023)
This study explores the implementation of green banking practices in Bank Syariah Indonesia(BSI) through the lens of Islamic economic ethics and sustainable finance principles. Theresearch seeks to understand how Islamic banking institutions integrate environmentalresponsibility within their financial operations, investment decisions, and corporate governancestructures. Using a qualitative descriptive approach, data were collected throughdocumentation, literature review, and secondary reports from regulatory authorities and BSI’ssustainability publications. The findings indicate that BSI has adopted various environmentallyconscious initiatives such as green financing, paperless transactions, and eco-efficientinfrastructure. However, the implementation remains partially instrumental, focusing more onregulatory compliance than on transformative commitment to sustainability. From an Islamicperspective, these efforts resonate with the principles of Maqashid al-Syari’ah—particularly thepreservation of life (hifz al-nafs) and wealth (hifz al-mal)—but require deeperinstitutionalization through strategic alignment with the Sustainable Development Goals (SDGs)and Islamic Environmental Governance. The study contributes to the growing discourse onIslamic sustainable finance by emphasizing that true green banking must embody not onlyenvironmental prudence but also spiritual accountability and social justice.